Innovation Processes in Business Networks Managing Inter-Organizational Relationships for Innovational Excellence - Ricciardi, Francesca. (Advances in Information Systems and Business Engineering,, 2014)
In today’s networked economy, each organization is more and more shaped by the system of its long-term business interactions. Innovation processes cannot be successfully designed and managed unless the complex influences of business networking on innovation processes and innovation-related performances are clearly understood. But extant theories on business networks are fragmented, and each of them, taken singularly, provides only partial or poor understanding of the impacts of business networking on innovation performances. Based on qualitative research on three exemplary worst practices and on expert panel discussion and validation, Francesca Ricciardi develops novel quantitative models in this theory-building work to explain innovation performances in different inter-organizational networks.  Contents Possible Positive and Negative Impacts of Business Networking on Innovation and Excellence Sustainable Altruism for Business Networking Ecology of Innovation in Organizational Settings Motivations for Business Networking Innovational Effectiveness of Different Network Types: Theory Building and Testable Models Target Groups Researchers, students, and practitioners in the fields of  information science and management science The Author Francesca Ricciardi has been a lecturer in "ICTs and the Information Society" and other similar subjects at the Catholic University of Milan, Italy, since 1998. The Editors The series Advances in Information Systems and Business Engineering is edited by Ulrike Baumöl, Jan vom Brocke and Reinhard Jung.